Characteristics of value-based health and social care from organisations' perspectives (OrgValue): a mixed-methods study protocol. Issue 4 (27th April 2018) - Ansmann, Lena; Hillen, Hendrik Ansgar; Kuntz, Ludwig; Stock, Stephanie; Vennedey, Vera; Hower, Kira Isabelle
Abstract : Introduction: Health and social care systems are under pressure to organise care around patients' needs with constrained resources. Several studies reveal that care is constantly challenged by balancing economic requirements against individual patients' preferences and needs. Therefore, value-based health and social care aims to facilitate patient-centredness while taking the resources spent into consideration. The OrgValue project examines the implementation of patient-centredness while considering the health and social care organisations' resource orientation in the model region of the city of Cologne, Germany. Methods and analysis: First, the implementation status of patient-centredness as well as its facilitators and barriers—also in terms of resource orientation—will be assessed through face-to-face interviews with decision-makers (at least n=18) from health and social care organisations (HSCOs) in Cologne. Second, patients' understanding of patient-centredness and their preferences and needs will be revealed by conducting face-to-face interviews (at least n=15). Third, the qualitative results will provide the basis for a quantitative survey of decision-makers from all HSCOs in Cologne, which will include questions on patient-centredness, resource orientation and determinants of implementation. Fourth, qualitative interviews with decision-makers from different types of HSCOs will be conducted to develop a uniform measurement instrument on the cost and service structure of HSCOs. Ethics and dissemination: For all collected data, the relevant data protection regulations will be adhered to. Consultation and a positive vote from the ethics committee of the Medical Faculty of the University of Cologne have been obtained. All personal identifiers (eg, name, date of birth) will be pseudonymised. Dissemination strategies include a feedback report as well as research and development workshops for the organisations with the aim of initiating organisational learning and organisational development, presenting results in publications and at conferences, and public relations. Trial registration number: DRKS00011925.